Hubungan Indonesia – Amerika yang Tidak Mudah - Suryohadiprojo, Sayidiman (Indonesian Journal of International Law, 2006)
In this era of Globalization relation among states have become much more important than before. No nation can afford to isolate itself without harming its national interests. Among the relations of Indonesia with many nations in the world, relation with the US definitely belongs to the most important ones, many factors are bringing about this necessity, in particular geostrategic factors. However, Indonesia-US relations have never been an easy matter, ever since the proclamation of the Republic Indonesia in 1945. The US wants to influence developments in Indonesia, aiming to bring it on its side. Indonesia-US relations imporved in 1965 when Indonesia defeated a communist coup and terminated the existence of the Indonesian Communist Party PKI which was the largest communist party in the world putside the communist bloc. Closer relations between Indonesia and the US started to flourish, enabling Indonesia to start economic developments, although without leaving its non-alignment policy. An important development affected Indonesia-US relations when the US on September 11, 2001 had experience a terrorist attack on the World Trade Center in New York and the Pentagon by a Muslim group calling itself Al Qaeda under the leadership of Osama bin Laden. Improvement of Indonesia-US relations very much depends on the establishment of an effective and stable governent in Indonesia, which is able to end confusion, instability and disorder, and demonstrate good governance to improve the national economy, social and political stability.